2019
DOI: 10.1007/s11769-019-1092-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Organization of Innovation in the Oil Equipment Manufacturing Industry: Case of Dongying, China

Abstract: As innovation and technological change have become increasingly important for the competitiveness and sustainable growth of firms, cooperative innovation is now crucial for traditional industries in the context of globalization. This paper proposes a framework for analyzing the spatial pattern of cooperative innovation for traditional industries in developing countries. Based on in-depth interviews with 35 firms in the oil equipment manufacturing industry in Dongying City, China, this study argues that differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…The center of gravity model can be used to summarize the spatial center of gravity change trajectory of geographic elements [ 50 ], with the help of which this paper analyzes the center of gravity migration direction and distance of high-level Grade A tourist attractions in the YRD urban agglomerations with the following formulas: where X and Y denote the coordinates of the center of gravity of the tourist attractions, X i and Y i are the coordinates of each study unit, and W i is the number of tourist attractions in the i th study unit.…”
Section: Research Area Methodology and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The center of gravity model can be used to summarize the spatial center of gravity change trajectory of geographic elements [ 50 ], with the help of which this paper analyzes the center of gravity migration direction and distance of high-level Grade A tourist attractions in the YRD urban agglomerations with the following formulas: where X and Y denote the coordinates of the center of gravity of the tourist attractions, X i and Y i are the coordinates of each study unit, and W i is the number of tourist attractions in the i th study unit.…”
Section: Research Area Methodology and Datamentioning
confidence: 99%
“…The center of gravity model can be used to summarize the spatial center of gravity change trajectory of geographic elements [50], with the help of which this paper analyzes the center of gravity migration direction and distance of high-level Grade A tourist attractions in the YRD urban agglomerations with the following formulas:…”
Section: Center Of Gravity Model and Standard Deviational Ellipsementioning
confidence: 99%
“…To improve the undesired fatty acid composition of B. napus, the low erucic acid variety "Oro" and the low-glucosinolate variety "Bronowski" are utilized for breeding improvement. The ratio of cultivars with double-low characteristics (low erucic acid and glucosinolate) in China has surpassed 90%, enabling the cultivation of high-yielding double-low hybrid B. napus (Wang, 2010). By 2021, B. napus seed production reached 14.7 million tons, accounting for over one-third of the national oilseed crop production in China.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have found that the total number of rural migrants has been increasing [40]. The main agglomeration area for rural migrants is the eastern coastal region [41][42][43], with their distribution in the city overlapping with the industrial layout to a large extent [44][45][46]. The distance factor is an obstacle to the migration of the rural population [47].…”
Section: Introductionmentioning
confidence: 99%